The Development of Students’ Language Competence in English Lessons - Dilshoda Sabirova Abrorovna, Allamurodova Sabohat Ibodullayevna (International Journal of Advanced Science and Technology, 2020)
In the article, teachers face certain difficulties due to the lack of didactic and scientific methodological bases for the use of media in the teaching of foreign languages in the classroom at different stages of the higher education system, their independent use outside the classroom. The development of a methodology for the effective use of media in teaching foreign languages in the system of continuing education is one of the important factors in meeting the requirements of state educational standards and increasing the effectiveness of education. is to develop an effective methodology.